The Relationship Between Prenatal Distress And Pregnant Women's Readiness for Labor at PMB Imelda, Lebak District - Imelda .; Wintarsih . (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2023)
Preparation for childbirth is everything that is understood and prepared in terms of welcoming the birth of pregnant women, prenatal distress in pregnancy has a direct impact on the fetus. Psychological disorders can affect the physical and mental health and well-being of the mother and her baby, this psychological condition is related to the baby's development process. The purpose of this study was to determine the relationship between the level of prenatal distress and delivery readiness at PMB Imelda, Lebak Regency in 2022. The research design used correlation analytic methods using a cross sectional approach. The population in this study were pregnant women in PMB Imelda, totaling 40 people. The type of sampling in this study is total sampling. Data were taken using PDQ and P4K questionnaires. The results showed that of the 32 respondents who had high prenatal distress, 70.0% of the respondents had unprepared labor readiness and of the 8 respondents with low prenatal distress, 7.5% were unprepared for delivery. The results of the Chi Square test showed that there was a significant relationship between prenatal distress and delivery readiness (p = 0.002). Thus the level of prenatal distress affects the readiness of the mother in childbirth. There needs to be an effort to improve maternal readiness in childbirth by implementing a program to increase readiness in childbirth to reduce prenatal distress.